New data on poorly known species of the genus Leia Meigen (Diptera, Mycetophilidae) from the Palaearctic region - Polevoi, Alexei; Salmela, Jukka (Zootaxa, 2016)
New data on four poorly known species of the genus Leia Meigen (L. nigricornis van Duzee, L. flavipennis Laštovka & Matile, L. iturupensis Zaitzev and L. rufiptera Ostroverkhova) are presented. Detailed redescriptions and terminalia figures are provided. Leia nigricornis is reported for the first time from the Palaearctic region and L. automnala Ostroverkhova & Grishina is found to be a junior synonym of L. flavipennis. A variation in the male terminalia of L. bimaculata Meigen is illustrated, based on specimens from several European countries.